Scholarship on and from the Margins: Festschrift in Honor of Resil B. Mojares - Aguilar Jr., Filomeno V. (Archīum Ateneo, 2019)
A motif that runs through thearticles in this special double issue in honor of Resil B. Mojares is the fecundity of the geographic and social margins. Mojares himself celebrates the margin as a “good place to be in” for a writer, who, he emphasizes, must not lapse into isolationism and parochialism. Thearticles in this issue exemplify scholarship from and on the margins, which are expansive in orientation, yielding fresh insights that challenge current interpretations and giving rise to new historiographies.KEYWORDS: MARGIN • PERIPHERY • HISTORIOGRAPHY • RESIL MOJARES